Grapyak value sociodrama technique group guidance guidebook for teaching students interpersonal communication skills - Sofa, Ilma Ainu; Setiyowati, Arbin Janu; Eva, Nur (Univeritas Papua, 2024)
This research and development aims to produce a guidebook for guidance and counseling teachers. Teachers can use this guide to provide group guidance services using sociodrama techniques of Grapyak Semanak value to develop interpersonal communication skills at school. This research uses research and development methods with the ADDIE model. The results of the validation analysis by material and learning media experts obtained 80.6%, which had very valid qualifications so that the product did not need to be revised. Meanwhile, a result of 3.6 was obtained for cultural expert validation, which has very valid qualifications and does not need to be revised. The test results obtained from prospective users were 97.7%, who had very valid qualifications, so effectiveness tests could be carried out. From the effectiveness test using one group pretest-posttest and carrying out the Wilcoxon test, it was obtained that the p-value was <0.05, which means that there was a change after the intervention was carried out. The research concluded that the group guidance book on sociodrama techniques has good value for developing interpersonal communication skills in the very good category based on aspects of product acceptability. The product effectively empowers students' interpersonal communication skills at Madrasah Aliyah based on the results of limited field tests.